Performance analysis on an air-conditioning system installed with and without a fuzzy logic thermostat in an office building - Yau, Yat Huang; Chang, C.P. (SAGE Publications, 2018)
The current research presents the study of the proposed thermostat setting developed in the previous work through a numerical simulation project using transient system simulation tool. The transient system simulation tool code is used to integrate the fuzzy logic to optimise a room thermostat with the multi-zone building model (Type56a). A set of equations is designed in the transient system simulation tool project to represent the fuzzy logic control system of the proposed thermostat setting. The performance analysis for the air-conditioning system installed with and without the application of the control system in terms of the operative zone temperature, the sensible cooling demand, the solar radiation, and the internal gains for a thermal zone for recent years or 2000s, and for the years 2020, 2050 and 2080 were comprehensively examined. Estimations of both predicted mean vote and predicted percentage of dissatisfied persons of the zone were also investigated. The findings indicate that a considerable amount of sensible cooling demand of approximately 8420 kJ/h or equivalent to 3.54% can be saved with the application of the proposed thermostat setting. The predicted mean vote is in the range from −0.22 to 0.72 with its average between 0.20 and 0.26 for the AC system installed with fuzzy logic control. These results further suggest that the thermal comfort of occupants can be improved taking into account their activity level, clothing insulation, indoor air temperature, air velocity, mean radiant temperature and relative humidity.